Study of the diagnostic value of a polymerase chain reaction for early diagnosis of experimental tuberculosis of bones and joints - Golka, Taras (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The purpose of the present work was to study the diagnostic value of a polymerase chain reaction (PCR) in a new experimental model of tuberculous gonitis, created by the authors, and examine peculiarities in the clinical-pathomorphological course of tuberculosis of bones and joints (TBJ). Features of the clinical-pathomorphological course of tuberculous disease of joints were studied as result of an experiment, conducted on guinea pigs with use of an original procedure. The analysis of results of the above research made it possible to reveal that the diagnostic sensitivity of PCR was 80 % at the prearthritic stage of the disease development and 100 % at its arthritic one. At the same time, the specificity of the chosen technique was 100 %, thereby enabling us to draw a conclusion that the use of PCR of synovial fluid in the arsenal of diagnostic methods for patients with TBJ is reasonable.